Improving the energy efficiency of solar systems for obtaining water from atmospheric air - Kholodkov, Andrey; Osadchuk, Eugeniy; Titlov, Alexandr; Boshkova, Irina; Zhihareva, Nataliya (Eastern-European Journal of Enterprise Technologies, 2018)
We considered problems of water scarcity elimination in arid regions of the planet and analyzed modern water producing systems. We showed the prospects of obtaining of water from atmospheric air directly while cooling it below the dew point using refrigeration units. We proposed to use absorption-type cooling systems with a water-ammonia solution as a working liquid as cooling units in regions with an excess of solar energy. We noted that low energy characteristics of heat-using refrigeration cycle, with main problems associated with non-calculated losses of refrigerant (ammonia) during transportation through AWRU refluxer hamper a widespread use of absorption water-ammonia refrigerating units (AWRU) in systems for obtaining of water from atmospheric air. This contribution is particularly noticeable in operation of AWRU in a wide range of outdoor air temperatures. We performed modeling of heat and mass exchange processes of a lifting section of an AWRU refluxer to find methods for elimination of ammonia transportation losses. At the heart of model representations were equations of heat and mass balances, and we took into account resistance of a diffusion process at radial movement of a vapor flow to a wall of a refluxer in modeling. A preliminary analysis of thermal resistance of reflux film showed its small contribution to the total resistance and we ignored it subsequently. As a result of modeling, we found a significant (up to 36 °C) temperature difference between a flow inside a refluxer and its wall. Experimental studies of a serial AWRU confirmed the modeling results. The obtained results made possible to propose the original design of a heat-insulating casing of an AWRU refluxer with variable thermal resistance with a corresponding change in the outside air temperature. This gave possibility to increase energy efficiency from 18 to 36 % and productivity of systems for obtaining of water from atmospheric air.